Caveats of the internal transcribed spacer region as a barcode to resolve species boundaries in Diaporthe. Issue 1 (January 2022) - Hilário, Sandra; Santos, Liliana; Phillips, Alan J.L.; Alves, Artur
Abstract: Species in Diaporthe are largely reported as important plant pathogens. Identification of species in this genus has been complemented by morphological and molecular features. However, one important factor delaying this process is the struggle to formulate robust species concepts to create adequate international phytosanitary measures. Regardless of the wide use of the internal transcribed spacer (ITS) rDNA region, established as the primary DNA barcode for fungi, the tendency for intraspecific variation has been reported, misleading interpretation of phylogenetic analyses. Therefore, the present study aimed to illustrate, using specific examples, how the ITS region may be problematic for species delimitation. We showed that the ITS region is highly variable, with strains of Diaporthe malorum and Diaporthe novem falling into more than one clade, which if analyzed on their own, would be likely recognized as distinct taxa. Divergent ITS paralogs were also proven to coexist within the genome of D. novem . We also suggest that ITS may have escaped from concerted evolution or has undergone a duplication event. Furthermore, this study reports for the first time the existence of a putative hybrid in the genus Diaporthe . Our findings offer new clues towards the intraspecific and intragenomic variation in the ITS region, raising questions about its value for barcoding, i.e., identifying species in the genus Diaporthe . Therefore, we recommend that the ITS region be analyzed cautiously and always compared for congruence prior to description of novel taxa. Highlights: The ITS region of rDNA in Diaporthe may have escaped from concerted evolution. The ITS region presents intraspecific and intragenomic variation. Divergent ITS paralogs were shown to exist within the genome of Diaporthe novem. This study reports the first putative hybrid in the genus Diaporthe.